"I Had to Jump through a Lot of Hoops": How Working Mothers in Student Affairs Navigate Institutional Policies and Student Affairs Norms. Issue 1 (2nd January 2022) - McKinnon-Crowley, Saralyn; Bukoski, Beth; Black, Victoria; Burmicky, Jorge; Molina, Veronica; Chacon, Krysta
Abstract : In this instrumental case study, we explored the experiences of working mothers in student affairs and how their situated realities are shaped by institutional and professional norms, including commonly understood written and unwritten practices. We conducted interviews and focus groups with 21 mothers working full-time at a research-intensive university in the South. We crafted themes to illustrate how ideal worker norms, inequality regimes, and the maternal wall were persistent concerns for the mothers in our study. Mothers had to make decisions based on inadequate institutional policies while the institution simultaneously benefited from skills they imported from motherhood to student affairs work. Given the condition of federal and state policies, we offer implications for institutional and unit changes to better meet mothers where they are, accommodate their unique needs, and provide pathways for them to continue contributing meaningfully to the field.